2010
DOI: 10.1165/rcmb.2009-0168oc
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Induces Chemotactic and Prosurvival Effects in Eosinophils

Abstract: Thymic stromal lymphopoietin (TSLP) is highly expressed by bronchial epithelial cells and skin keratinocytes in allergic diseases. TSLP acts as a master switch for allergic inflammation through the activation of dendritic cells and mast cells for initiating inflammatory type 2 T-helper lymphocyte responses. To elucidate the immunological cascades of epithelium/keratinocyte-eosinophil-mediated allergic inflammation, we examined the modulating effects of TSLP on human eosinophils. Expression of TSLP receptor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 54 publications
10
127
3
2
Order By: Relevance
“…Similarly, Wong et al [26] have demonstrated that TSLPR was expressed in eosinophils isolated and cultured from the blood of healthy volunteers. Consistent with these findings, our study demonstrated that TSLP was expressed in epithelial cells, plasma cells and inflammatory cells in the nasal mucosa of patients in both the ECRS and NECRS groups.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Wong et al [26] have demonstrated that TSLPR was expressed in eosinophils isolated and cultured from the blood of healthy volunteers. Consistent with these findings, our study demonstrated that TSLP was expressed in epithelial cells, plasma cells and inflammatory cells in the nasal mucosa of patients in both the ECRS and NECRS groups.…”
Section: Discussionmentioning
confidence: 94%
“…This leads to the inhibition of CCR3-mediated chemotaxis, and ultimately to the suppression of eosinophilic inflammation (Struyf et al 1999;Yan et al 2012). Finally, analogous to the inflammation-amplification mechanisms used by other acute inflammatory cells, thymic stromal lymphopoietin (TSLP) -stimulated eosinophils also produce CCL2, CXCL1, and CXCL8 promoting further influx of inflammatory monocytes and neutrophils (Wong et al 2010).…”
Section: Eosinophilsmentioning
confidence: 99%
“…9 Recently, TSLP has been shown to promote survival, cytokine and chemokine release, and up-regula-tion of adhesion molecules in human eosinophils. 10 These observations suggest that TSLP can orchestrate allergic inflammation by activating cells of both the adaptive and the innate immune systems. In accord with this notion, transgenic mice expressing TSLP under the regulation of the keratinocyte-specific promoters for keratin-14 11 or keratin-5 12 develop atopic dermatitis-like skin lesions, with inflammatory infiltrates including eosinophils and lymphocytes, and also exhibit pronounced splenomegaly, lymphadenopathy, and elevated serum levels of IgE and IgG1 antibodies.…”
Section: Rabgef1mentioning
confidence: 99%